Cochrane Database of Systematic Reviews 2007
DOI: 10.1002/14651858.mr000008.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Methods to increase response rates to postal questionnaires

Abstract: Health researchers using postal questionnaires can increase response rates using the strategies shown to be effective in this systematic review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
136
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(147 citation statements)
references
References 319 publications
10
136
1
Order By: Relevance
“…We acknowledge the limitation of this evaluation, and the response rate to our survey is a potential source of bias. The response rates to health surveys average around 60% 28 when using maximal techniques, 29 with response rates of about 50% typical of surveys with two reminders. 30 There are many confounding factors determining response rates to surveys that are epidemiologically based, but a crucial key factor is the resampling of populations that have 517 (10) 19 (5) 76 (13) <0.001…”
Section: Discussionmentioning
confidence: 99%
“…We acknowledge the limitation of this evaluation, and the response rate to our survey is a potential source of bias. The response rates to health surveys average around 60% 28 when using maximal techniques, 29 with response rates of about 50% typical of surveys with two reminders. 30 There are many confounding factors determining response rates to surveys that are epidemiologically based, but a crucial key factor is the resampling of populations that have 517 (10) 19 (5) 76 (13) <0.001…”
Section: Discussionmentioning
confidence: 99%
“…Although incentives have been shown to increase response rates in many surveys, a number of studies have reported no significant improvement [3]. Taking a closer look at these studies, it appears that several epidemiologic surveys actually report non-significant negative results [7,13,20,21].…”
Section: Discussionmentioning
confidence: 99%
“…However, declining response rates are becoming a serious issue when using self-administered questionnaires and this may lead to non-response bias [1,2]. Considerable efforts have been made to increase participation in selfadministered questionnaires [3].…”
Section: Introductionmentioning
confidence: 99%
“…1 A large systematic review that was ongoing at that time had identified hundreds of randomized trials of strategies to improve the response rates to postal surveys. 2,3 This review, which identified trials evaluating 98 different ways of increasing response rates to postal questionnaires, found that monetary incentives, the use of recorded delivery, a teaser on the envelope (such as a comment suggesting that the addressee may benefit if they open it) and a more interesting questionnaire topic could more than double the odds of a response. 3 The review included some trials of the influence of the status of the signatory on response rates but it had not identified any trials assessing the value of a knighthood (see Discussion).…”
Section: Introductionmentioning
confidence: 99%